Culture shock and adaptation: International students’ academic and social experiences at a State Islamic University (Passage: Journal of English Language and Literature, 2025)
Culture shock is described as the psychological discomfort that arises from experiencing new cultural settings, leading to feelings of confusion, anxiety, and disorientation. This research investigates the culture shock faced by international students and looks into how they cope with it. Through a qualitative method, data were collected via semi-structured interviews, observations, and reflective journals, and analysed using NVivo software. The study involved four international students—two from Thailand and two from the Philippines—who studied at the State Islamic University. The results highlighted five main areas of culture shock: (1) affective aspects, such as disorientation and loss of social support; (2) behavioral problems, including misunderstandings across cultures; (3) cognitive dissonance like language barriers and social obstacle to interaction; (4) intra psychological elements such as homesickness and limited language skills; and (5) academic challenges related to teaching styles, course material, and lack of information of institutional rules. The study reveals that university requires improved support systems for international students. Institutions should provide clear cultural orientation, improve cross-cultural communication training, and offer continuous academic and emotional support. These steps help students adjust more easily and prepare universities to work with diverse cultural backgrounds.